Segmentasi Pasar Media: Jangan Ikut Ritme Pesaing - Wicaksono, Bayu (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstraksi:Tagline Suara Merdeka "Perekat Komunitas Jawa Tengah" is not in line with the local mediadevelopment today. When many newspapers focus on the territory of the district/city or formerresidency, Suara Merdeka consistent on the people of Central Java. It also inconsistent with theregional autonomy policy, the which is based on the district/city, not the province. For the dilemmaarises Suara Merdeka, between targeting on Central Java and information needs of local level. Itsneed balancing between the two, so the newspaper is able to survive, and even win the competition. Theequilibrium model can be used as a lesson for other media to stick to the principle of differentiation,is not provoked rhythm competitors.